Modelos e decomposição Dantzig-Wolfe no abastecimento centralizado de postos de trabalho - Diego Fernandes Pantuza Moura (2018)
The present study aims to address the problem of centralized supply of jobs. The motivation for the study is the practical situation observed in a large automobile industry located in the state of Minas Gerais. In more specific terms, the model studied aims to determine the best size of packaging to be used to move each item demanded by the workstation within a planning horizon, in order to minimize the associated total costs. In the study it will be presented a formulation to cover a greater number of practical situations, will be also proposed heuristics to find better solutions to the problem, and a Dantzig-Wolfe Decomposition to obtain better lower bounds for real instances analyzed.